Model of Environmental Education and Psychological Factors Influencing to Global Warming Alleviation - Thiengkamol, Nongnapas (Richtmann Publishing, 2012)
Environmental education has been accepted and applied for encouraging the global citizens to take a responsiblepractice through their behavior changing in daily life activity. This might be an effective and rapid change to decrease thegreenhouse gases via the awareness raising, attitude and belief adjusting, skill and participation increasing including realpractice in daily living.The populations were 35,010 undergraduate students of the first semester of academic year 2011 ofMahasarakham University. The simple random sampling was used to collect the sample for 450 undergraduate students withproportion according to fields of study. The questionnaire was employed as instrument for data collecting. LISREL was used formodel verification. Results illustrated as Equation 1and 2 as followings. Considering on structural model confirmatory factorswas able to explain the variation of endogenous factors of Environmental Education (EE) to caused Environmental Behaviors forGlobal Warming Alleviation (BEH) with 97.5 percents and the variation of endogenous factor of Environmental Education (EE)with 90.5 percents. Therefore, the equation 1 and 2 can be written as followings.BEH = 0.56 *PsT + 0.38*PsS + 0.52* EE …………..…………..(1)(R2 = 0.975)EE = 0.45*PsT + 0.47*PsS …………………..…………..………..(2)( R2 = 0.905)